Aplikasi Pengelolaan Arsip Surat: Studi Kasus di Sekolah Dasar Negeri - Desti Yuvita Sari; Nur Rohman; Raden Muhamad Firzatullah (JUSIFO : Jurnal Sistem Informasi, 2023)
This research aims to utilize computers as a tool for implementing information technology to enhance an individual's role as an information intermediary in tasks and processes, including the collection, transmission, processing, interpretation, storage, organization, and utilization of correspondence data to obtain high-quality information. The initial implementation of letter archive management involved manual recording of letters each day using a book, leading to insufficient detailed records of both incoming and outgoing letters, often resulting in difficulties in retrieving correspondence and impeding operational efficiency. The system development method employed is the waterfall method, characterized by the requirement to complete each step before advancing to the next, ensuring a systematic approach. The stages include software requirement analysis, design, coding, testing, and maintenance. This study addresses the challenges associated with manual recording of correspondence data using books, overcoming issues of inaccuracy and lack of precision in recording both incoming and outgoing letters through the implementation of an archive management application. With the integration of this application, the letter data processing becomes more accurate, detailed, efficient, and prompt, especially with the structured storage of data in a database.